'Pushing back': People newly diagnosed with dementia and their experiences of the Covid‐19 pandemic restrictions in England. (2nd September 2022) - Dixon, Josie; Hicks, Ben; Gridley, Kate; Perach, Rotem; Baxter, Kate; Birks, Yvonne; Colclough, Carmen; Storey, Bryony; Russell, Alice; Karim, Anomita; Tipping, Eva; Banerjee, Sube; et al.
Abstract: Background and Objectives: Research into people with dementia's experiences of the Covid‐19 pandemic has tended to focus on vulnerabilities and negative outcomes, with the risk of reproducing a discourse in which people with dementia are positioned as passive. Informed by concepts positioning people with dementia as 'active social agents', we aimed to identify the pandemic‐related challenges faced by people recently diagnosed with dementia and examine the ways in which they actively coped with, and adapted to, these challenges. Research Design and Methods: In‐depth interviews with 21 people recently diagnosed with dementia, recruited through an existing national cohort. Data was analysed thematically using Framework. Findings: Key challenges included reduced social contact, loneliness and loss of social routines; difficulties accessing and trusting health services; dementia‐unfriendly practices; and disparate experiences of being able to 'get out' into the physical neighbourhood. People with dementia responded to challenges by maintaining and extending their social networks and making the most of ' nodding acquaintances '; learning new skills, for communication and hobbies; supporting others, engaging in reciprocal exchange and valuing connection with peers; seeking help and advocacy and challenging and resisting dementia‐unfriendly practices; maintaining and adapting habitual spatial practices and being determined to ' get ou t '; and employing similar emotional coping strategies for the pandemic and dementia. Conclusions: Support for people with dementia, especially during public health crises when carers and services are under pressure, should involve utilising existing capacities, appropriately supporting the acquisition of new knowledge and skills, 'safety‐netting' through the availability of a named professional, advocacy and support and use of 'check‐in calls' and creating supportive social and environmental circumstances for people with dementia to sustain their own well‐being. Key points: Research conducted directly with people with dementia, exploring their lived experiences, is helpful for understanding the ways in which they respond as 'active social agents' to challenges in their lives. People recently diagnosed with dementia reported a range of challenges and negative experiences associated with the Covid‐19 pandemic including loneliness and loss of social routines; difficulties in accessing and trusting health services; dementia‐unfriendly practices and challenges ' getting out ' into the physical neighbourhood. They responded to challenges by maintaining and extending social networks; learning new skills; supporting others and engaging in reciprocal exchange, including with peers; seeking help and advocacy and challenging and resisting dementia‐unfriendly practices; maintaining and adapting habitual spatial practices; and employing a range of emotional coping strategies. Support for people with dementia during public health crises should aim to create social and environmental circumstances that enable people with dementia to help sustain their own well‐being.